Stress-Testing The Indonesia Economic Sectors by Shock on ITS Macroeconomic Variable ( An Analysis of Firm-Wide Probability of Default) - Munich, Adrian; Surya, Budhi Arta (The Indonesian Journal of Business Administration, 2013)
Indonesia has kept its two years of living dangerously in 1997-99. During 1997-99’s crisis, Indonesia had the most exceedingly awful impact contrasted with the other countries that encountered the Asian crisis. The recovering cost, in both cash-worth cost and inarticulate expense, was greatly towering. This accompanying figure was depicting Indonesian real sectors and external sectors from 1994-2004. Several Indonesia’s real sectors and external indicators, since 1997-99’s crisis until present, never fully-recovers to its previous low-rate condition. Economic downturn was authenticated by a decreasing wealth, parallels with the shrinkage of money power, for both buying and paying power. As we know, Indonesian 1997-99’s economic crisis has made the rupiah, Indonesian currency, take its free fall against US Dollar. Thirty years of uninterrupted economic condition of a good country with its predictable economic growth rate in South East Asia, was shocked by its own foreign exchange rate.